Kecerdasan Spiritual Dengan Tingkat Stres Perawat Pada Masa Covid-19 Di RSUD Kabupaten Tangerang - Ayu Pratiwi; Yunike Edmaningsih; Tita Yulia; Achmad Abdul Lutfbis (Jurnal Kesehatan, 2022)
ABSTRACT Background: pandemic covid-19 cause nurses to experience stress due to unstable emotions so easily angry, worried about exposed to covid-19, many duties and responsibilities can increase the workload so it takes high spiritual intelligence to lower stress levels. Research objective: to find out whether there is the relationship of spiritual intelligence with a nurse’s stress level on during covid-19 at RSU Kabupaten Tangerang. research metode: Using research quantitative descriptive correlation to find out variable spiritual intelligence with nurse’s stress level. Sampling technique are using total sampling with sample numer 107 respondents. research results: the data analysis technique used is chi square test on spiritual intelligence with nurse’s stress level the result are p-value 0,000 <0,05 with pearson correlation 0,403 wich mean is relationship rate moderate. Conclusions : That there is a relationship of spiritual intelligence with a nurse’s stress level on during covid-19 at RSU Kabupaten Tangerang. suggestion: The Nurses can do stress management, improve knowledge of high spiritual intelligence to lower stress levels.